An Isolable Gallium‐Substituted Nitrilimine and its Reactivity with B−H, Si−H and B−B Bonds. Issue 4 (7th December 2021) - Kassymbek, Aishabibi; Gusev, Dmitry G.; Dmitrienko, Anton; Pilkington, Melanie; Nikonov, Georgii I.
Abstract: Reaction of the Ga(I) compound NacNacGa (9 ) with the diazo compound N2 CHSiMe3 affords the nitrilimine compound NacNacGa(N‐NCSiMe3 )(CH2 SiMe3 ) (10 ). Carrying out this reaction in the presence of pyridine does not lead to C−H activation on the transient alkylidene NacNacGa=CHSiMe3 but generates a metallated diazo species NacNacGa(NHN=CHSiMe3 )(CN2 SiMe3 ) (13 ) that further rearranges into the isonitrile compound NacNacGa(NHN=CHSiMe3 )(N(NC)SiMe3 ) (15 ). Reactions of 10 with the silane H3 SiPh and the borane HBcat furnished products of 1, 3 addition to the nitrilimine moiety NacNacGa{N(ER n )NCSiMe3 }(CH2 SiMe3 ), whereas reaction with the diborane B2 cat2 gave the product of formal nitrene insertion into the B−B bond. DFT calculations suggest that the interaction of 9 with N2 CHSiMe3 proceeds through intermediate formation of an alkylidene compound that undergoes CH activation with a second molecule of N2 CHSiMe3 . Insertion into the B−B bond likely proceeds through an initial 1, 3‐addition of the diborane, followed by boryl migration to the former nitrene center. Abstract : Reaction of diazomethane N2 CHSiMe3 with the Ga(I) compound NacNacGa affords the nitrilimine complex 10 that undergoes 1, 3‐addition reactions with silane and borane to give products 16 and 17 but an unusual 1, 1‐addition of diborane (Bcat)2 (cat=catecholate) to give the diborylamide compound 18 . DFT calculations provide insight into the mechanism of formation of compound 9 and 18 .